Kompetensi Sosial Guru SMK Negeri 1 Rao Selatan Kabupaten Pasaman - Ridhol Haq (Universitas Negeri Padang, 2020)
The problem in this study is the low level of social competence possessed by South Negeri 1 Rao Vocational School teachers in Pasaman Regency. This study aims to find out how much social competency possessed by South Rao 1 South Vocational School teachers in Pasaman Regency. This type of research is quantitative. The population in this study were all students of SMK Negeri 1 South Rao Pasamanyaitu, class X and XI, totaling 556 people. Sampling in this study using the Proportionate Stratified Random Sampling technique, so that the sample in this study amounted to 226 people. Data collection techniques using a questionnaire or questionnaire. Data analysis techniques used descriptive statistical analysis. The results showed that, social competence of teachers in terms of the ability to communicate with students by 79.4% or in the category of